Targeted Next-Generation Sequencing of Cancer Genes in Advanced Stage Malignant Pleural Mesothelioma: A Retrospective Study. Issue 3 (March 2015) - Lo Iacono, Marco; Monica, Valentina; Righi, Luisella; Grosso, Federica; Libener, Roberta; Vatrano, Simona; Bironzo, Paolo; Novello, Silvia; Musmeci, Loredana; Volante, Marco; Papotti, Mauro; Scagliotti, Giorgio V.
Abstract : Introduction: Malignant pleural mesothelioma (MPM) is a rare malignant disease, and the understanding of molecular pathogenesis has lagged behind other malignancies. Methods: A series of 123 formalin-fixed, paraffin-embedded tissue samples with clinical annotations were retrospectively tested with a commercial library kit (Ion AmpliSeq Cancer Hotspot Panel v.2, Life Technologies, Grand Island, NY) to investigate 50 genes plus other two, BRCA1-associated protein-1 (BAP-1) and neurofibromatosis-2 (NF2), frequently altered in MPM. DNA was obtained from tissues after manual microdissection and enriched for at least 50% cancer cells. Variations affecting protein stability or previously correlated to cancer, more frequently identified (≥25 patients with at least 10% of allelic frequency), were subsequently evaluated by Sanger sequencing. Immunohistochemistry staining for BAP1 and NF2 proteins was also performed. Results: The commonest genetic variations were clustered in two main pathways: the p53/DNA repair ( TP53, SMACB1, and BAP1 ) and phosphatidylinositol 3-kinase–AKT pathways ( PDGFRA, KIT, KDR, HRAS, PIK3CA, STK11, and NF2 ). PIK3CA:c.1173A>G mutation, STK11:rs2075606 (T>C), or TP53:rs1042522 (Pro/Pro) was significantly associated with time to progressive disease (TTPD; all p values < 0.01). Furthermore, the accumulation of genetic alterations correlated with shorter TTPD and reduced overall survival (TTPD p value = 0.02, overall survival p value = 0.04). BAP1 genetic variations identified were mainly located in exons 13 and 17, and BAP1 nonsynonymous variations were significantly correlated with BAP1 protein nuclear localization. Conclusion: Next-generation sequencing was applied to a relatively large retrospective series of MPM using formalin-fixed, paraffin-embedded archival material. Our results indicate a complex mutational landscape with a higher number of genetic variations in the p53/DNA repair and phosphatidylinositol 3-kinase pathways, some of them with prognostic value.